Kuleli Askeri Lisesi`nde görev yapan öğretmenlerin hizmet içi eğitim ihtiyacı hangi seviyededir - Altun, Metin (My University, 2001)
This research was made with the aim of determinig the level of needs for in service education of the teachers who work in Kuleli Military High School. For this purpose, a survey was prepared to determine the degree of their beliefs on the necessity of in-service education, the needs for in-service education of their own professions and for teaching career. As a result, (1) teachers believe that in-service education is a process which will last through their professional life and they must undergo such educational processes in definite time intervals,(2) experienced teachers found the improvements on their own professions enough but less experienced ones not that much so they need in-service education, (3) teachers need in-service education on using educational materials, (4) in terms of teaching career, as the teachers found themselves enough on using the methods of techniques of teaching, motivating students to lecture, and using the techniques of measuring and evaluating, they need in service education on making educational environment and students ready to lecture.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2001
Keywords: Kuleli askeri lisesi; Öğretmenlerin hizmet içi eğitim ihtiyacı